The Relationship Between IgM Anti Phenolic Glycolipid-1 Serum Levels and Bacterial Index in Multibacillary Leprosy Patients - Maulani, Adylla Nissya; Fitriyanti; Suzan, Raihanah (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
ABSTRACTBackground: Leprosy remains a public health concern in various countries, with approximately 250,000 new cases reported annually worldwide. Slit-Skin Smear results show the distribution of M. leprae in the skin and determine the degree of infectiousness and severity of multibacillary leprosy. PGL-1 antigens stimulate IgM antibody formation. Anti-PGL-I IgM indicates that the patient has an acute immune response or is actively suffering from leprosy. This study aims to determine the relationship between serum levels of anti-PGL-1 IgM and bacterial index (BI) values in multibacillary leprosy. Methods: This observational study employed a cross-sectional design. The research was conducted at Dr. Rivai Abdullah Leprosy Hospital and Sukajadi Public Health Center, Banyuasin District, South Sumatra Province. During February-November 2019, 30 study samples underwent Slit Skin Smear examination and serum level testing of IgM Anti PGL-1 antibodies using the ELISA method. Results: The findings showed that zero persons (0%) had anti-PGL-1 IgM values <605 μ/mL, and 30 people (100%) had anti-PGL-1 IgM values ≥605 μ/mL. BI scores <3 were found in 13 people (43.3%) and ≥3 in 17 people (56.7%). The study results demonstrated a significant correlation between anti-PGL-1 IgM levels and BI values in Multibacillary leprosy patients with p=0.036 (p<0.05). Conclusion: Higher bacterial index values correlate with increased serum levels of anti-PGL-1 IgM.Keywords: Anti PGL-1 IgM; Bacterial index; Slit skin smear